Introduction to the analysis, synthesis, and comparisons of endemic butterflies in Mexico - Trujano-Ortega, Marysol; Luis-Martínez, Armando; Vargas-Fernández, Isabel; Ávalos-Hernández, Omar; Llorente-Bousquets, Jorge (Zootaxa, 2024)
Endemic species are biological singularities whose relevance lies in their unique history and the information they provide about the history of the area where they are distributed. This is the first compilation study that brings together all the available information on endemics of butterflies, a highly diverse insect group in Mexico. Based on the records of 272 endemic taxa deposited in biological collections, we generate distribution maps for each taxon, and describe the patterns of endemic distribution. We analyze the results based on biogeographical provinces, vegetation types, and altitudinal levels. We compared these distribution patterns with those of endemic taxa of vertebrates, plants, and other insect groups in Mexico. The greatest number of endemic butterflies is in the southwestern portion of the country, in the Sierra Madre del Sur and the Pacific Lowlands. In terms of ecological distribution, endemism is distributed mostly at low and middle elevations in Seasonally Dry Tropical Forests, Temperate Forests and Mountain Humid Forests, the latter being of special importance due to its reduced extent in the country. The similarity in species composition groups the provinces into three clusters that generally agree with the Nearctic and Neotropical regions, and the Mexican Transition Zone. In addition, we describe the sampling biases at the family and subfamily levels as well as the undersampled biogeographical provinces, considering the estimation of endemic richness and the heterogeneity of the area. With this information, taxa and priority areas are identified to allocate the sampling effort and thus increase knowledge about the endemic taxa of the country. Nymphalidae were the family with the most records and endemic taxa, while Lycaenidae were the least endemic family in the country. We propose the Sierra Madre Occidental as the highest priority for directing the sampling effort for endemic butterflies. Finally, we discuss the historical and ecological causes of the distribution of endemic butterflies and compare it to the distribution patterns of endemic vertebrates and plants. Insects represent most biodiversity worldwide and are relatively poorly known compared to vertebrates or vascular plants. However, insects are just as threatened by ecosystem modification as other taxa. This work contributes to the urgent need to record biodiversity and thus prioritize conservation and resource management schemes.